MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS XI-B1 SMK-PP NEGERI SAREE MELALUI PENDEKATAN MATEMATIKA REALISTIK - Yustina Yustina (Jurnal Sains Riset, 2017)
Yustina (2014). Improving Learning Motivation of Students in XI-B1 SMK-PP Negeri Saree through Realistic Mathematics Education. This study aims to analyse the improvemet of students’ motivation and to describe the activities of students during Math class using realistic mathematics education. This study is classroom action reasearch. It was conducted in XI-B1 SMK-PP Negeri Saree school year 2013/2014 within 22 pupils that were consisted of 13 boys and 9 girls. This study was done in two cycles. The result of study in cycle I showed that only 4 students (18%) achieved the comprehensiveness. On the other hand, in cycle II, 20 students (91%) completed the target grade. The enhancement of students’ motivation can be seen from students’ comment from one through five statements. In the first statement, 12 students (55%) responded strongly agree with the learning process, 8 students (36%) agree, and 2 students (9%) concerned doubtful. Second statement showed that 14 students (64%) were strongly agree with the learning approachment, 6 students (27%) were agree, and only 2 students (9%) were doubtful. From statement 3, 6 students (27%) responded with strongly agree, 2 students (9%) agree, 4 students (14%) doubthful and 2 students (9%) responded not agree. In the fourth statement, 11 students (50%) said strongly agree with the lesson taught, 10 students (46%) commented agree, and only one student (4%) was doubtful. Statement five, indicated that 11 students (50%) stated strongly agree with the class and the other 11 students (50%) voted agree. Based on study data analysis result, it can be concluded that the implementation of realistic mathematic education is able to improve students’ motivation in class XI-B1 of SMK-PP Negeri Saree. Key words : Learning with Realistic Mathematics Education, Motivation of Students, Activities of Student